Drug Logistics Management at the Pharmacy Installation of the Sigi District Health Office - ninda syafiraramadhani; Novi Inriyanny Suwendro; Miftahul Haerati Sulaiman; Stefiani Bengan Laba (Preventif : Jurnal Kesehatan Masyarakat, 2026)
Drug logistics management is essential in the health service system to ensure the availability of medicines in the appropriate type, quantity, time, and quality. Ineffective drug logistics management can lead to medicine stockouts and reduced service quality. Sigi Regency in Central Sulawesi Province still faces challenges in the availability of essential medicines, which remains below 80% of the strategic plan target. This study aims to analyze drug logistics management at the Pharmaceutical Installation of the Sigi Regency Health Office, covering planning, procurement, storage, distribution, disposal, and control of medicines. This study used a qualitative case study design. Data was collected through in-depth interviews, observations, and document observations, with 6 informants.. Data analysis was conducted descriptively through data reduction, data presentation, and conclusion drawing. The results indicate that drug logistics management at the Pharmaceutical Installation of the Sigi Regency Health Office has not been optimally implemented. Problems were identified in planning due to discrepancies in needs data and budget limitations, delays in procurement, substandard storage conditions, and distribution constraints related to geographical conditions. In addition, the disposal and control of medicines have not been optimally carried out. Therefore, improvements are required in drug planning based on consumption data and remaining stock, strengthening procurement coordination, meeting storage standards, adjusting distribution to geographical conditions, and implementing proper disposal and control through routine recording and reporting to ensure effective and efficient medicine availability in Sigi Regency.